GAP-43 and BASP1 in Axon Regeneration: Implications for the Treatment of Neurodegenerative Diseases - Chung, Daayun; Shum, Andrew; Caraveo, Gabriela (Frontiers in Cell and Developmental Biology, 2020)
Growth-associated protein-43 (GAP-43) and brain acid-soluble protein 1 (BASP1) regulate actin dynamics and presynaptic vesicle cycling at axon terminals, thereby facilitating axonal growth, regeneration, and plasticity. These functions highly depend on changes in GAP-43 and BASP1 expression levels and post-translational modifications such as phosphorylation. Interestingly, examinations of GAP-43 and BASP1 in neurodegenerative diseases reveal alterations in their expression and phosphorylation profiles. This review provides an overview of the structural properties, regulations, and functions of GAP-43 and BASP1, highlighting their involvement in neural injury response and regeneration. By discussing GAP-43 and BASP1 in the context of neurodegenerative diseases, we also explore the therapeutic potential of modulating their activities to compensate for neuron loss in neurodegenerative diseases.